IMPLEMENTASI SISTEM HIDROPONIK PEMBENIHAN CABE MERAH DENGAN BERBASIS GREEN HOUSE DI KABUPATEN PANDEGLANG - Alimuddin, Alimuddin (Lembaga Pengabdian kepada Masyarakat Universitas Muslim Indonesia, 2019)
Red chili (Capcicum Annum L) is one of the horticulture plants that has high economic value, can provide employment and improve the standard of living of farmers. Red chili is one of the leading commodities of the national and Banten provinces, where the planting is almost spread throughout the territory of Indonesia. Red chili is a commodity that is needed by all levels of society. Red chili is rich in carbohydrates, protein, fat, flavonoids, capsaicin, minerals, water, fiber and rich in vitamin C and provitamin A. The need for red chili always increases along with population growth and diverse needs. Pandeglang is known as one of the largest vegetable cultivation areas in Banten Province. The need for seeds for one hectare planting area requires around 2-3 Kg of chili (300–500 gr of chili seeds) with high economic value. The aim is to implement a hydroponic and green house system for Red Chili hatchery cultivation in Pandeglang district. Methods used The application of technology carries out technological engineering in the development of red chilli cultivation in the hydroponic and green house planting media to improve the quality of red chilli seeds in Pandeglang district. Tahapan is the dissemination of community service implementation to industry partners with program objectives in Mandalawangi sub-district, hydroponic kit assembly, and building green houses. Results, the implementation of hydroponic making activities for the cultivation of red chilli seeds and the making of green houses, FGDs or training and mentoring of red chilli seedlings, FGD Making Hydroponic Kits, FGDs making Green House.